-6x+-px=-z+2

Simple and best practice solution for -6x+-px=-z+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+-px=-z+2 equation:


Simplifying
-6x + -1px = -1z + 2

Reorder the terms:
-1px + -6x = -1z + 2

Reorder the terms:
-1px + -6x = 2 + -1z

Solving
-1px + -6x = 2 + -1z

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6x' to each side of the equation.
-1px + -6x + 6x = 2 + 6x + -1z

Combine like terms: -6x + 6x = 0
-1px + 0 = 2 + 6x + -1z
-1px = 2 + 6x + -1z

Divide each side by '-1x'.
p = -2x-1 + -6 + x-1z

Simplifying
p = -2x-1 + -6 + x-1z

Reorder the terms:
p = -6 + -2x-1 + x-1z

See similar equations:

| 10x-3=-82 | | 3/4(g+7)=15 | | 48x^2-56x-24=0 | | -3(m-1)+4m=-8+9+4m | | -17-2=3+4x+5 | | 3(4z-8)=12 | | 4(v-1)=-9v+9 | | 6z-3z+5-4=3z-5+4 | | -2(d+6)-3(4d-2)=22 | | 4x-8=11y-1 | | p=5/9*350000 | | -4(x-4)=28+8x | | 2g-12=16-10h | | 13.50/3 | | -45-5+2b=10 | | 175m-75m-53625=55000-175m | | -12x-3x=-8 | | Z=6x+px+2 | | 4x-45=7(x-9) | | -(4-6n)=n+11 | | B-1/2=b/3+7 | | ((7x+6)(2x+10))/((6x+2)(7x+5)) | | y=6/7x-2 | | -7+14k-13+-(-5k)+3= | | x/-8=-1-(-3) | | 3x=3(8-7x) | | 20.5=(w/3600)(703) | | 22-8x=-5(5x-1) | | -2(-3x+3y)=-2(-27) | | 3xy+3x=6 | | (11x)/6+2/3=2x | | 80x+2250=70x+5600 |

Equations solver categories